STRATEGI PENERAPAN E-GOVERNMENT DI KOTA PEKANBARU - Desriani Paulina Nainggolan; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In response to the development of the world today almost all aspects of the activities are always related to information. In the organization of development and maximize the utilization of technology. This change has changed the perspective of each person in doing various activities one of which is the activities of government agencies. The structure of service providers and institutional readiness and the demands of the times for future public services in the form of e-government.Pekanbaru Municipal Government is one of the Regency / Municipal Government in Indonesia has implemented electronic government in running its government affair for the realization of good governance. In the case of this e-government development program Pekanbaru Municipal Government through the Office of Information Communications Statistics and Pekanbaru City Persandian have a role to manage the implementation of electronic data or e-government. However, the aspect especially in the utilization of internet media or internetanan network in Pekanbaru City Government largely has not been utilized optimally.The purpose of this research is to find how dept of information communication strategy statistika and persandian city pekanbaru in the application of e-government in the city pekanbaru.The study is done by using the method qualitative study assessment data with a sort of descriptive set.In data collection, researchers used technique interview, observassi, and documentation of using key informants a source of information.This research result indicates that strategy the application of e-government in the city pekanbaru who guided by presidential no. 3 years 2003 on policy and e-government development strategy and in accordance with the mayor pekanbaru no. 107 years 2016 via the communication information statistika and persandian city pekanbaru been going on and under development .But in implementation of the done by the agency communication information statistika and persandian city pekanbaru not maximum for infrastructure is weak and the lack of human resources to hit the acceleration e-government .Keywords: Strategy, E-Government, Pekanbaru City